Pemberdayaan Masyarakat Kelurahan Kota Baru Melalui Pelatihan Pembuatan Pestisida Nabati Daun Pepaya untuk Pengendalian Hama Serangga dan Kutu Daun - Deni Sabriyati; Putri Nabila; Susilo Ragel Setiawan; Risma Situmorang; Maergy Putri Lianti; Dewi Melinda Hutabarat; Fitria Rahmadani; Velvi Thiana Anasky; Sry Unihartati Saogo; Mochammad Faiz Agil Nurfikri; Rivaldo Saragih (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
The use of chemical pesticides in modern agriculture in Indonesia has a negative impact on the environment and health. To address this issue, students from the 24th Community Service Program (KKN) of Raja Ali Haji Maritime University (UMRAH) held a training session on making plant-based pesticides from papaya leaves in Kota Baru Village, Bintan. This activity aimed to provide environmentally friendly and easy-to-apply pest control solutions to local farmer groups. The training involved agricultural extension workers from the Bintan Regency Food Security and Agriculture Office as resource persons. The results of this training are expected to increase farmers' knowledge and skills in utilizing papaya leaves as natural pesticides, reducing the use of chemical pesticides, and realizing more sustainable and environmentally friendly agriculture in Kota Baru Village. Despite obstacles in community participation, this activity succeeded in sparking farmers' interest in applying plant-based pesticides in their crop cultivation.